IgG4 disease as a differential diagnosis of head and neck squamous cell carcinoma. (17th March 2021) - Swansbury, Andrew; Pilkington, Richard J. J.; Kennedy, Matthew; Adams, James R.
Abstract: Aim: To highlight the need to include IgG4 disease in the differential diagnosis of head and neck squamous cell carcinoma (SCC). Method: We will present two cases which recently presented to the Maxillofacial Department at the RVI hospital, Newcastle, UK. One had a large palatal ulceration and one had a soft tissue mass on the orbital floor with extensions into the maxillary antrum. Results: Both cases had clinical and radiographic features indicative of SCC, however, following biopsy a definitive diagnosis of IgG4 disease was made. The patients were treated successfully medically via MDT (Multidisciplinary Team) with rheumatology. This involved the use of immunosuppressants including Prednisolone and Rituximab. Conclusions: Treatment for head/neck SCC typically involves large resections with significant impacts upon a patient's quality of life. Therefore, it is important that alternative diagnosis is considered and excluded. We hope these cases show that IgG4 disease should be on this list.